An Analysis of Direct Observation and Camera Trapping in the Survey of Large Mammals in Gashaka Gumti National Park, Nigeria - Schombi, O. S; Buba, U; Febnteh, E. B (International Journal of Integrative Sciences, 2023)
Large mammalian species community was surveyed using camera trap and direct observation at Kwano forest of Gashaka-Gumti National Park, Nigeria. Information on large mammalian species composition, richness and abundance were gathered using motion triggered white flash digital trial cameras. A total of 638 independent events with twenty six (26) large mammalian species were photographed during camera trapping, and thirteen (13) animal species were sighted during direct observation method. The large mammals relative abundance index (RAI) ranged from 0.07 (waterbuck) to 10.47 (baboon). The results suggest that the park still holds a good number of large mammals. Human activities of any kind should be prevented, and there should be periodic large mammals monitoring programs using camera traps and drones in and around this sector of GGNP